Analysis of Catechins in Gambir West Sumatra - Alif Gita Arumsari (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
Gambir contains functional compounds that are included in the class of polyphenol compounds. The polyphenol compounds in gambir are mainly catechins, a natural substance that has antioxidant properties. The purpose of this study was to obtain catechin compounds from Gambir extract, to determine the solvent concentration and the right extraction temperature to obtain catechin compounds in Gambir, and to increase the selling value of Gambir latex in the Farmer community. To get the results of catechins in Gambir, this research was carried out using the infundation method. The yield of the extract was mostly found at a solvent concentration of 45% ethanol, a temperature of 105 oC and a time of 3 hours, namely 81%. Qualitative test using FeCl3 reagent can be seen that in the filtrate extracted from gambir there are catechins which show a blackish green color when dropped with FeCl3